Increasing Lecturers’ Interest in Research and Community Service - Widiya Avianti; Indri Putri Utami (Inaba of Community Services Journal, 2024)
Tri Dharma Universities is the strength of the education world to develop all elements in this non-profit organization. The role of lecturers as human resources who produce quality graduates is needed. Lecturers’ quality development includes the ability to carry out the Tri dharma of higher education through teaching, research, and dedication to society. The importance of motivation and brainstorming is organized through workshop events, and time is not an obstacle, the concept of online workshops that present material about research and dedication to the society with the support of expert lecturers in the field of research as a resource person to increase lecturers' interest is an effective activity to develop lecturers’ interest and motivation to carry out Tri dharma in every term.